1968
DOI: 10.1063/1.1656188
|View full text |Cite
|
Sign up to set email alerts
|

Neutron Scattering from Magnetite below 119°K

Abstract: A neutron-scattering experiment to look for spin-wave excitation-energy changes of magnetite at the transition point 119°K showed no such change. During this work we discovered, however, that the lowtemperature structure gives rise to weak extra neutron-diffraction lines that can be indexed as (h, k, l±!) in cubic indices. From the observed neutron polarization sensitivity of the intensities and the increasing structure factors with increasing sinO/X, we conclude that the extra reflections are not directly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

1972
1972
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(22 citation statements)
references
References 4 publications
1
21
0
Order By: Relevance
“…21,22 The observation of monoclinic lattice symmetry was also confirmed by a single-crystal x-ray study, 23 whereas the observation of a magnetoelectric effect indicated even lower P 1 symmetry in the low-temperature phase. 24 Although, clear evidence of the monoclinic lattice symmetry below T V was obtained, small atomic displacements have not been fully resolved so far.…”
Section: Introductionmentioning
confidence: 60%
“…21,22 The observation of monoclinic lattice symmetry was also confirmed by a single-crystal x-ray study, 23 whereas the observation of a magnetoelectric effect indicated even lower P 1 symmetry in the low-temperature phase. 24 Although, clear evidence of the monoclinic lattice symmetry below T V was obtained, small atomic displacements have not been fully resolved so far.…”
Section: Introductionmentioning
confidence: 60%
“…There the formal valence of V ion is 3.5, and the one of Fe on B sites is 2.5 (the valence of Fe ions on A sites is 3), i.e., they have to exist in equal combinations of V 3+ and V 4+ , or Fe 2+ and Fe 3+ . Notice, however, that recent studies contradict the direct application of the ice (tetrahedron) rule to LiV 2 O 4 and Fe 3 O 4 [61,62,63,64,65,66,67,68,69,70,71,72,73,74,75]. For the recent reviews on spinel materials consult, e.g., [76,77,78,79].…”
Section: Ice Modelsmentioning
confidence: 99%
“…In particular, the observation of half-integer reflections at (h, k, l + 1 2 ) points indicated the doubling of the unit cell along the c axis. 6 Further diffraction studies by neutron, 7,8 x-ray, 9 and electron 10 scattering established the monoclinic symmetry of the low temperature (LT) phase realized below T V . Indeed, the number of inequivalent A and B atomic positions found by nuclear magnetic resonance (NMR) for the phase below the VT 11,12,13 agrees with the monoclinic structure.…”
Section: Introductionmentioning
confidence: 99%
“…4 and Fe +2. 6 . Providing a convincing evidence in favor of such a state has been a challenge for several direct probing methods including the resonant xray scattering.…”
Section: Introductionmentioning
confidence: 99%